2012
DOI: 10.2119/molmed.2012.00053
|View full text |Cite
|
Sign up to set email alerts
|

The Calm Mouse: An Animal Model of Stress Reduction

Abstract: Chronic stress is associated with negative health outcomes and is linked with neuroendocrine changes, deleterious effects on innate and adaptive immunity, and central nervous system neuropathology. Although stress management is commonly advocated clinically, there is insufficient mechanistic understanding of how decreasing stress affects disease pathogenesis. Therefore, we have developed a "calm mouse model" with caging enhancements designed to reduce murine stress. Male BALB/c mice were divided into four grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 55 publications
5
31
0
Order By: Relevance
“…Previously [23], we have shown that caging environments that mimic elements of a natural murine habitat such as providing access to an exercise wheel can substantially influence various aspects of mouse physiology. To increase the degree to which animal studies successfully translate, it may be worth investigating whether standard housing conditions appear to be artificial and more suited for convenience, rather that reproducing more natural housing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previously [23], we have shown that caging environments that mimic elements of a natural murine habitat such as providing access to an exercise wheel can substantially influence various aspects of mouse physiology. To increase the degree to which animal studies successfully translate, it may be worth investigating whether standard housing conditions appear to be artificial and more suited for convenience, rather that reproducing more natural housing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Control mice were housed under standard conditions recommended by IACUC for the maintenance of mice: 4 animals per cage in polycarbonate cages (189 3 297 3 128 mm 3 ) provided with standard corn cob bedding, autoclaved tap water and irradiated food ad libitum. In accord with published procedures, 29 stress reduction was achieved in the treatment group by housing the same number of mice in larger polycarbonate cages (257 3 483 3 152 mm 3 ) provided with the following enrichment items: two polycarbonate tunnels (Bio-Serv) to allow tunneling behavior, two paper nest boxes (Bio-Serv) and nesting material (compressed Envirodry Eco-bedding paper strips, Fibercore) for shelter and enhancement of nesting behavior. All enrichment items were autoclaved prior to use.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Using in vitro studies with cancer stem cell like cells (CSCs) enriched by spheroid formation assays from three NSCLC cell lines in conjunction with environmental and enrichment strategies reported to generate the “calm mouse”, an animal model for stress reduction and well‐being, in athymic mice carrying NSCLC xenografts, our current data provide evidence, for the first time, that stress neurotransmitters significantly increase the number of CSCs via cAMP‐driven stimulation of the SHH pathway and ALDH‐1 and that these responses are inhibited by pharmacologically or psychologically‐induced increases in GABA or opioid peptides.…”
mentioning
confidence: 99%
“…Environmental enrichment has been described as an efficient paradigm to reduce stress in laboratory rodents 9 . Here, we bred mice in standard or enriched environment prior to EAE induction and exposure to repeated acute stress ( Figure 3A-B).…”
Section: Resultsmentioning
confidence: 99%